DEVELOPMENT OF NANOCELLULOSE FROM BIOMASS USING IONIC LIQUIDS WITH CARBOXYLATED NITRILE BUTADIENE RUBBER COMPOSITE - ROZY, NUR ALIAH (2023)
The current study deals with the problem of environmental and biological impacts caused by gloves as it has been increasing due to global pandemic. In this regard, crystalline nanocellulose (CNC) was extracted from biomass such as sugarcane bagasse by using Cholinium Lysinate ionic liquid in order to develop nvironmentally friendly material for gloves.